Transexualidade e esporte: uma análise dos discursos midiáticos jornalisticos - Nascimento, Rodrigo Henrique de Jesus (2020)
In this research, we aim to analyze the journalistic discourses regarding the insertion of trans people in sports and their experience, as well as their social, historical and political relationship. Competitive sports have attracted both the interest of athletes and spectators, in addition to the interest of the state as a policy, the economy as a business, and other factors. What we see in common when looking at sports is the intersection of body dimensions, gender and sexuality. Therefore, we were interested in thinking about this aspect in contemporary times. A striking fact is the tensions generated by institutions, coaches and athletes regarding the participation of trans athletes in high performance sports, tensions generated by the good performance of volleyball player Tifanny Pereira de Abreu, a trans woman active in the Brazilian volleyball league. To achieve the proposed objective, we take the case of this player as a research field. We analyzed ten journalistic articles, published between March 2019 and March 2020 that dealt with the insertion and permanence of the athlete in Brazilian volleyball. The research has a qualitative nature and the contents of the journalistic articles were studied using content analysis as a method. Finally, the results show that the arguments that aim to prohibit the participation of trans athletes do not have solid and coherent bases, being the result of the personal beliefs and prejudices of cis men who are based on religious beliefs and transphobia. The athlete became the target of transphobia, coming from different places, especially from politicians in the conservative wing. It was found that there is a lack of studies that aim to discuss and analyze the inclusion of trans athletes in sport from their different bodies.